Lazer power supply based on multiphase resonance converters - Kazanivsky, Mikhailo (Видавництво Львівської політехніки, 2010)
The laser power supply construction structure has been proposed on the base of multiphase resonance converter
Keywords: laser power supply; multiphase resonance converter